2019
DOI: 10.1016/j.materresbull.2018.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and piezoelectric properties of porous lead-free 0.5Ba(Ca0.8Zr0.2)O3-0.5(Ba0.7Ca 0.3)TiO3 ceramics

Abstract: Porous barium calcium zirconate titanate 0.5Ba(Ca0.8Zr0.2)O3-0.5(Ba0.7Ca0.3)TiO3 (BCZT) lead-free ferroelectric ceramics were fabricated via a burnt polymer spheres (BURPS) technique by introducing corn starch as the pore-forming agent. The effect of porosity on the microstructure, dielectric, and piezoelectric properties of the porous materials were investigated. An increase in porosity from 10 % to 25 % resulted in an increase in the hydrostatic charge coefficient (dh), which was 140 to 560 % higher than tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…6a, the TC increased slightly with an increase in porosity, which was attributed to stress relaxation near the pores. 122 A similar trend was also observed in freeze-cast porous PZT ceramics, 88 as shown in Fig. 6b.…”
Section: Dielectric Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…6a, the TC increased slightly with an increase in porosity, which was attributed to stress relaxation near the pores. 122 A similar trend was also observed in freeze-cast porous PZT ceramics, 88 as shown in Fig. 6b.…”
Section: Dielectric Propertiessupporting
confidence: 79%
“…The decrease in the piezoelectric coefficients can be ascribed to the reduced efficiency of the poling process, which leads to a reduced piezoelectric response 122 ; this stems from a decrease in the remnant polarization since due to the complex electric field distribution on porous ferroelectrics. The piezoelectric dij coefficients of porous ferroelectric ceramics are therefore usually lower than dense materials.…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%
“…Moreover, Zhang et al, [102] investigated the piezoelectric and dielectric properties of lead-free porous 0.5Ba(Ca0.8Zr0.2)O3-0.5(Ba0.7Ca0.3)TiO3 (BCZT) ceramics. They reported that the porosity decreased the relative permittivity while a denser material increased the permittivity.…”
Section: Volume Fraction Of the Fillermentioning
confidence: 99%
“…Lead is toxic and detrimental both to humans as well as to the environment, the use of lead-based piezoelectric material is discouraged these days, and search for several lead-free alternative materials is encouraged (Vaish, 2013;Vaish, 2013, 2014). Several lead-free piezoelectric materials, which are poled ferroelectric ceramics, have been reported in the literature such as (Maeder et al, 2004;Zhang et al, 2019). KNLNTS, due to its higher piezoelectric strain coefficient, is a promising lead-free piezoelectric material that can be used as an alternative to lead-based piezoelectric materials (Berger et al, 2005;Kwok et al, 2010) for sensing and energy harvesting applications.…”
Section: Introductionmentioning
confidence: 99%